Depression, Anxiety and Stress among Obese Patients with Chronic Illnesses: Prevalence and Associated Factors in North East Malaysia - Hassan, Raihan; Mohd Zulkifli, Maryam; Ahmad, Imran; MohdYusoff, Siti Suhaila (Bangladesh Journal of Medical Science, 2019)
Introduction: Concomitant obesity and chronic medical illness is a significant health problem in Malaysia and worldwide. The comorbid psychological impact in obese patients is associated with a social stigma and low self-esteem. The aim of this study was to determine the prevalence and the factors associated with depression, anxiety and stress in obese patients with chronic medical illnesses attending an outpatient clinic. Methods: This was a cross-sectional study among obese patients with chronic medical illnesses presenting at the Universiti Sains Malaysia Hospital outpatient clinic. A total of 274 patients were involved. The 21-item Depression, Anxiety and Stress Scale questionnaire was used, and the results were evaluated using single and multiple logistic regression analyses. Results: The prevalences of depression, anxiety and stress among the obese patients with chronic medical illnesses were 13.9%, 23.4% and 10.9%, respectively. Younger age [p=0.003, adjusted odds ratio (AOR),1.0; 95%confidence interval (CI),0.91–0.98], unemployed employment(p=0.013, AOR,3.7;95% CI,1.32–10.09) and smoking (p=0.022, AOR,3.2; 95% CI,1.18–8.55) were associated with depression. No formal education (p=0.011, AOR,5.7; 95%CI,1.49–21.89), high body mass index (p=0.029, AOR,1.1;95% CI,1.01–1.13) and family history of psychiatric illness (p=0.018, AOR,5.1; 95% CI,1.33–19.56) were associated with anxiety. Stress was strongly associated with females (p=0.004, AOR,5.0; 95% CI,1.70–15.13) and smoking(p=0.002, AOR,6.5; 95% CI,2.03–20.7). Conclusion: Interestingly, younger age group was associated with depression. Current smokers, no education, family history of psychiatric illness and female sex were significantly associated with anxiety and stress. This notifies new emerging knowledge on factors associated with obese patients that would empower the development of effective preventive strategies for it. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.252-259